Keseimbangan Asam-Basa pada Pasien dengan Kronis Ginjal Penyakit PGK : Narative Review - Suandika, Made; Aurellia Septia Pramadani, Diandra; Liyan Wulandari, Putri; Naylatus Syarofah, Fadiyah (Pustaka Galeri Mandiri, 2026)
Chronic kidney disease (CKD) is a major global health burden characterized by progressive loss of renal function and impaired acid–base regulation resulting from reduced hydrogen ion excretion and limited bicarbonate regeneration.These abnormalities frequently lead to chronic metabolic acidosis, contributing to disease progression and increasing perioperative risk in surgical patients.This narrative review evaluates the impact of intravenous fluid choice, specifically 0.9% saline versus balanced crystalloids, on acid–base homeostasis in CKD patients undergoing surgery. A critical analysis was performed using ten peer reviewed articles from reputable journals, focusing on the pathophysiology of acid–base disturbances in CKD, biochemical effects of perioperative fluids, and clinical outcomes related to fluid selection.The findings indicate that 0.9% saline, due to its high chloride concentration, is associated with hyperchloremic metabolic acidosis and may worsen renal function.Conversely, balanced crystalloids contain metabolizable buffers such as lactate or acetate, preserve a more physiological strong ion difference, enhance acid–base stability, and are linked to a lower risk of acute kidney injury.In conclusion, balanced crystalloids are preferable to saline for perioperative fluid management in CKD patients, as they support better acid–base balance and may reduce postoperative complications. Individual patient factors and electrolyte status should guide perioperative therapy decisions.